Evaluasi Dampak Program Intervensi di Sektor Pertanian - Muhammad Ibnu (Fakultas Pertanian, Universitas Timor, 2022)
Interventions in the agricultural sector need to be evaluated whether they are really successful and have the expected impact on beneficiaries, such as farmers. However, the definition of impact evaluation has varied considerably in the last two decades. Some empirical studies are also still biased in evaluating the impact, and this is related to the method used. This research has three objectives. First, to review the definition of impact evaluation according to the literature. Second, to identify sources of bias in impact evaluation studies. Third, to review empirical studies on impact evaluation, which have different results, especially from the methodology used. Empirical studies that serve as 'cases' in the agricultural sector are studies on the impact of coffee standards and certification. Thus, this research method is a theoretical literature review supported by empirical research results. The literature review reveals that one of the most common definitions of impact evaluation is that evaluation relates to counterfactual, which is a comparison between what actually happened and what would have happened in the absence of the intervention. Inappropriately designed counterfactuals are a major source of bias in impact evaluation, in addition to validity threats. Based on a review of empirical studies on the impact of coffee standards and certification, it is concluded that some studies have more reliable results than others. Studies with more reliable results use reliable counterfactuals, so as to minimize impact evaluation bias through an ‘apple-to-apple’ comparison between the intervention group and the control group.